2001
DOI: 10.1029/2000jc900163
|View full text |Cite
|
Sign up to set email alerts
|

Structure and modeling of surf zone turbulence due to wave breaking

Abstract: Abstract. The turbulence structure under breaking waves in the surf zone is investigated through reference to experimental measurements and turbulence closure modeling. This includes a unique set of recent turbulence measurements that have extended into the roller area through the application of digital particle image velocimetry. Measurements highlight the surface roller as the primary agent for turbulence production, from where it is transported downward principally because of turbulent diffusion. Reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 45 publications
4
29
0
Order By: Relevance
“…As discussed by Mocke [2001], a local equilibrium between dissipation and diffusion of TKE is associated with an exponential decay in the rate of dissipation in the form…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed by Mocke [2001], a local equilibrium between dissipation and diffusion of TKE is associated with an exponential decay in the rate of dissipation in the form…”
Section: Resultsmentioning
confidence: 99%
“…This is certainly the case for positions above the approximate trough level. Through an examination of the cross-shore distribution of depth averaged turbulent kinetic energy in a number of plane slope experiments, Mocke [2001] speculates that the transition region for roller development extends to approximately 75% of the break point water depth. Both, stations 1 and 2, fall in this region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surf zone is generally two to three wave heights deep, implying that breaking-wave-induced turbulence should be able to penetrate all the way to the sea bed. Indeed, the potential of breaking wave turbulence to entrain sediment has been observed in the laboratory (Nadaoka et al 1988;Okayasu et al 2002) and suggested from field observations (e.g., Voulgaris and Collins 2000;Aagaard and Hughes 2010) and numerical models (Mocke 2001). Many models of sediment transport, however, relate the entrainment of sediment from the sea bed to bed-generated turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is shown in [11,12] that surging breaker and field of turbulence velocities have dominating influence on processes in coastal zone such as wave damping, flows of mass and impulse, currents, and sediment transport. On small water, breakers interact with seabed plants and sediments.…”
Section: Introductionmentioning
confidence: 99%